Cliff outcrops used as condor communal roosts are local hotspots of occupancy and intense use by other bird species. (August 2016) - Lambertucci, Sergio A.; Ruggiero, Adriana
Abstract: Cliff outcrops are structural components of the environment that can maintain a large variety of wildlife; however, they are still rather overlooked in conservation planning. We evaluate whether cliffs used by the Andean condor ( Vultur gryphus ) for communal roosting are associated with local aggregations of other bird species, and if their presence in combination with other local (vegetation cover, plant species richness, topographic heterogeneity) and regional (distance to water) environmental variables play a significant role in the structuring of local bird diversity. We selected twenty-four localities in north-western Patagonia (Argentina) to compare the abundance and richness of birds across four habitat types: a cliff used as condor roost (CC), closest cliffs to CC not used for roosting with the same (SC) or different (DC) aspect and the vegetation matrix surrounding the cliffs (MA). This led to 264 fixed 100 m-radius points spread over 96 sampling sites. We recorded more individuals and species on cliffs than on MA; however, sample-based rarefaction curves showed that the high species richness observed on cliffs was actually the consequence of the high number of individuals recorded. Habitat type, vegetation cover and the richness of dominant vascular plants were the most important variables accounting the richness and abundance of birds. We concluded that condor roosts represent suitable habitats for the aggregation of individuals of other bird species thus leading to hotspots of occupancy and high species richness. Those cliffs should be reconsidered in the mapping of important conservation areas and for the proposal of mesofilter conservation strategies. Highlights: Cliffs, and particularly condor communal roosts, are used intensively by other bird species. The aggregation of individuals on communal roosts promotes high species richness. Vegetation cover increases the abundance and richness of birds on cliffs. Condor communal roosts can be used to identify local high bird diversity areas. Condor communal roosts should be considered in meso-filter conservation strategies.